Effect of Welding Parameters on Nanostructured Fe-(C, B)-(Cr, Nb) Alloys - Gramajo, Jonathan Nahuel (2019)
New nanostructured Fe-(Nb,Cr)-(C,B) multicomponent alloys have been developed for hardfacing application. They have better wear resistance than traditional Fe-Cr-C alloys. The nanoalpha- Fe, eutectic and hard carboborides phases of the weld metal usually show variations with the welding procedure. 6 test samples with different heat input were welded. It was observed that the percentage of eutectic phase and the distance between carboborides increased for the high heat input. Microhardness of eutectic phases showed a linear relationship with the spacing. Samples with high percentage of alpha-Fe phases showed a severe plastic deformation. Wear resistance was optimal for thinner eutectics phases. The presence of needles carboborides improved wear resistance.